2021
DOI: 10.1111/tbj.14208
|View full text |Cite
|
Sign up to set email alerts
|

Predicting postoperative complications following mastectomy in the elderly: Evidence for the 5‐factor frailty index

Abstract: Breast cancer remains the most commonly diagnosed cancer in women in the United States. 1 Surgical options include breast conservation surgery or mastectomy, with similar survival rates. 2,3 Patients who undergo mastectomy can subsequently decide to pursue immediate or delayed breast reconstruction. Postoperative complications of these procedures remain a major concern and lead to significant morbidity, including surgical site infection, skin flap necrosis, loss of implant, and need for reoperation. Complicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…27 In a 2021 study by Dammeyer et al, patients with mFI-5 scores of 2 or greater who underwent mastectomies demonstrated higher rates of postoperative complications. 28 This agrees with our findings that incremental increases in preoperative mFI-5 score are associated with a greater likelihood of developing complications postoperatively.…”
Section: Discussionsupporting
confidence: 92%
“…27 In a 2021 study by Dammeyer et al, patients with mFI-5 scores of 2 or greater who underwent mastectomies demonstrated higher rates of postoperative complications. 28 This agrees with our findings that incremental increases in preoperative mFI-5 score are associated with a greater likelihood of developing complications postoperatively.…”
Section: Discussionsupporting
confidence: 92%
“…It is with great interest that we read the manuscript by Dammeyer et al on the value and reliability of the 5-Factor Fragility Index Score (mFI-5) in predicting 30-day postoperative complications in patients undergoing mastectomies. 1 We commend the authors for using the American College of Surgeons National Surgical Quality Improvement Program (ACS-NSQIP) data base in an ingenious way in order to assess the validity of the mFI-5 for predicting complications after mastectomy. The ACS-NSQIP data base has been used extensively to study the short-term outcomes of mastectomies.…”
Section: Editorial On Predicting Postoperative Complications Following Mastectomy In the Elderly: Evidence For The 5-factor Frailty Indexmentioning
confidence: 99%
“… 11 This simplified version has been shown to yield consistent predictions of postoperative complications and mortality and has been validated in different cohorts undergoing various surgical procedures. 12 , 13 , 14 Despite this well-documented role of mFI-5 as an accurate risk stratification tool, its applicability and utility for predicting outcomes in patients with severe burns are yet to be determined. Therefore, we aimed to assess the predictive value of mFI-5 for complications and in-hospital mortality in a single-center burn population and to evaluate its potential role in burn-related risk stratification.…”
Section: Introductionmentioning
confidence: 99%